2018
DOI: 10.1371/journal.pone.0185087
|View full text |Cite
|
Sign up to set email alerts
|

A novel molecular toolkit for rapid detection of the pathogen and primary vector of thousand cankers disease

Abstract: Thousand Cankers Disease (TCD) of Juglans and Pterocarya (Juglandaceae) involves a fungal pathogen, Geosmithia morbida, and a primary insect vector, Pityophthorus juglandis. TCD was described originally from dying Juglans nigra trees in the western United States (USA), but it was reported subsequently from the eastern USA and northern Italy. The disease is often difficult to diagnose due to the absence of symptoms or signs on the bark surface of the host. Furthermore, disease symptoms can be confused with thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Although much of Putah Creek between Winters and Davis, California has been altered anthropogenically beginning in the late 1800s (Matheny et al, 1991), the reserve currently supports a fairly representative riparian forest, consistent with what existed pre-European settlement in the Central Valley (Griffin & Critchfield, 1976;Katibah, 1984 , 1997). The previous sampling from the reserve confirmed active infestations of P. juglandis and G. morbida (Oren et al, 2018). These data were corroborated by a visual survey of the reserve, which revealed significant crown dieback, especially among the larger diameter J. hindsii trees.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Although much of Putah Creek between Winters and Davis, California has been altered anthropogenically beginning in the late 1800s (Matheny et al, 1991), the reserve currently supports a fairly representative riparian forest, consistent with what existed pre-European settlement in the Central Valley (Griffin & Critchfield, 1976;Katibah, 1984 , 1997). The previous sampling from the reserve confirmed active infestations of P. juglandis and G. morbida (Oren et al, 2018). These data were corroborated by a visual survey of the reserve, which revealed significant crown dieback, especially among the larger diameter J. hindsii trees.…”
Section: Introductionsupporting
confidence: 68%
“…juglandis and G . morbida (Oren et al ., 2018). These data were corroborated by a visual survey of the reserve, which revealed significant crown dieback, especially among the larger diameter J .…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, these endophytic fungi grow faster than the agent of TCD and it is not uncommon that they completely overgrow G . morbida , thus masking its presence [ 24 ]. In fact, a G .…”
Section: Discussionmentioning
confidence: 99%
“…First, the fungus is difficult to isolate with traditional culture-based methods, since it grows very slowly and is easily overgrown in cultures by other fungi inhabiting the walnut’s surfaces and inner tissues. These fungi include common contaminants, commensals and endophytes, like those of Fusarium sp., whose role has yet to be defined [ 24 ]. Another hindrance in conventional identification of G .…”
Section: Introductionmentioning
confidence: 99%
“…One pathogen detection study (Lamarche et al 2015) reported on primers (GmF677/GmR878) based on the b-tubulin gene that were selective and sensitive for G. morbida detection in a real-time PCR protocol. More recently, microsatellite markers have been developed that are specific for the pathogen based on assays conducted with wood shavings (Oren et al 2018). Both these methods required specialized equipment; thus, we devised a PCR assay that was capable of being reproduced in a typical, basic diagnostic lab.…”
mentioning
confidence: 99%